Optimisation and application of the GH3.TRE.Luc Reporter Gene Bioassay to assess thyroid activity in drinking and source water - Aneck-Hahn, Natalie H. (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2017.